Talangkang Pag-Iisip: An Exposé of Its Positivity in the Lens of Students in a Selected University in Baguio City - Billote, William Jo Se; De Sagon, Gael Ann; Escoto, Marie Fe; Pableo, Arnel; Ponce, Ryan; Ponce, Trixie Elaine; Quibal, Joan; Quiloan, Aljon; Comaya, Mark Anthony; Ponce, Jessamine Marie (JPAIR Multidisciplinary Research, 2021)
Crab mentality is one of the common universal traits among many people. It is a behavior wherein a person feels jealous of the success, developments, achievements, and accomplishments of others. Some people who could not cope with their enviousness and jealousy may lead to committing actions that may deal negative impacts on the integrity, credibility, and social status of the person they are envious of, just to name a few. Although this may be universal and popular among many people, the difference lies in how this feeling is regulated and handled or managed by each individual. By seeing it as an admiration that will motivate them to become better individuals, certain people can turn this into something positive. The study aimed to expose the positive aspects and evaluate the source of crab mentality of fifteen (15) selected Special Education students in a selected University in Baguio City, Philippines. This sought to seek positive circumstances of crab mentality manifested by the students at home and in school. This is to change the perception of people that the crab mentality has only negative aspects as it also has good and positive attributes. Furthermore, this study will help professionals understand the positivist approach of crab mentality. This study employed pagtatanong-tanong, a Filipino psychology research method, which is an indigenous way of collecting or gathering data leading to a case study. The study conducted showed that the positive sides of the crab mentality being manifested at home and school leads to various factors.